2013
DOI: 10.1371/journal.pone.0069224
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Modafinil on Brain Resting State Networks in Young Healthy Subjects

Abstract: BackgroundThere is growing debate on the use of drugs that promote cognitive enhancement. Amphetamine-like drugs have been employed as cognitive enhancers, but they show important side effects and induce addiction. In this study, we investigated the use of modafinil which appears to have less side effects compared to other amphetamine-like drugs. We analyzed effects on cognitive performances and brain resting state network activity of 26 healthy young subjects.MethodologyA single dose (100 mg) of modafinil was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 57 publications
2
51
1
3
Order By: Relevance
“…Modafinil has already been used for the treatment of narcolepsy and other sleep disorders 8,9,10 . In recent years, psychostimulants have been used to promote cognitive enhancement, since they help the performace in areas such as attention and memory 11 . Previous studies have shown that this drug can significantly improve the performance in tests for executive functions, such as working memory, cognitive flexibility and planning, in healthy volunteers who were not sleep deprived 8 .…”
mentioning
confidence: 99%
“…Modafinil has already been used for the treatment of narcolepsy and other sleep disorders 8,9,10 . In recent years, psychostimulants have been used to promote cognitive enhancement, since they help the performace in areas such as attention and memory 11 . Previous studies have shown that this drug can significantly improve the performance in tests for executive functions, such as working memory, cognitive flexibility and planning, in healthy volunteers who were not sleep deprived 8 .…”
mentioning
confidence: 99%
“…In a previous study, we have found that a single dose administration of modafinil does not modify SN activity [14]. However, previous findings indicate that the anterior insula, a major SN hub [15], is activated by modafinil in methamphetamine addicts who were undergoing a reversal learning task [13].…”
Section: Discussionmentioning
confidence: 86%
“…In a previous study, we have observed that healthy young individuals, after modafinil administration, showed improvement in fluid reasoning as measured with Advanced Progressive Matrices (APM) [14], [27]. Previous imaging studies have indicated that SN nodes, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Elderly people who regularly exercise show brain volumes increases by ~2% in these critical areas while age-matched individuals who are less physically active undergo a 1.4% decrease in volumes (Erickson et al, 2010, 2011; Esposito et al, 2013). …”
Section: Non-pharmacological Interventionsmentioning
confidence: 99%